Influence of Infrastructural Choices Strategy on Organizational Performance of Cement Manufacturing Firms in Kenya - Karuga, Charles (International Journal of Strategic Management, 2024)
Purpose: To determine the influence of infrastructural choices strategy on organizational performance of cements manufacturing firms in Kenya. Methodology: A mixed methods approach was used in the investigation. The study utilized a concurrent triangulation research design. The unit of analysis comprised of seven (7) cement manufacturing firms, targeting all the 4192 employees from where a sample size of 365 employees was drawn. The data collection tools comprised of semi-structured questionnaires and interview guides. The interview guide was administered to the CEOs while the questionnaires were administered to the managers and non-managers. The study tools were piloted to assess their validity and reliability. The data was then analyzed both descriptively and inferentially using SPSS version 27. Quantitative data was analyzed using means and standard deviations while qualitative data was analyzed using content analysis. To make the number of variables more manageable, the data was subsequently subjected to exploratory factor analysis. Findings: The results of the study revealed that infrastructural choice strategies have been employed by cement manufacturing firms to a good extent. The regression results obtained also led to the rejection of the null hypotheses since infrastructural choice strategies were found to have a positive and significant influence on organizational performance. Unique Contribution to Theory, Policy and Practice: The study recommended, based on these results that the management of individual cement firms need to identify appropriate infrastructural choice strategies and leverage on them in order to achieve efficient and effective utilization of their scarce resources at organizational level.